2017
DOI: 10.1177/0033294116685866
|View full text |Cite
|
Sign up to set email alerts
|

Framing Effect in the Trolley Problem and Footbridge Dilemma

Abstract: The present study investigated the effect of dilemma type, framing, and number of saved lives on moral decision making. A total of 591 undergraduates, with a mean age of 20.56 (SD = 1.37) were randomly assigned to 12 groups on the basis of a grid of two dilemma types (the trolley problem or the footbridge dilemma) by three frames (positive, neutral, or negative frame) by two different numbers of workers (5 or 15 people). The main effects of dilemma type, frame, and number of saved workers were all significant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
35
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 43 publications
9
35
4
Order By: Relevance
“…Petrinovich & O'Neill (1996) found that participants were susceptible to the framing effect in the bystander scenario, and Pastötter et al (2013) showed that participants resisted the framing effect in the footbridge scenario. In line with these results, Cao et al (2017) confirmed that participants resisted framing manipulation in the 'footbridge scenario' while they were susceptible to the framing manipulation in the 'bystander scenario'. On the opposite, one study showed that participants resisted the framing manipulation in the 'bystander scenario' while they were susceptible to the framing manipulation in the 'footbridge scenario' (Broeders et al, 2011), which runs counter the aforementioned findings.…”
Section: Sinnott-armstrong 2011)supporting
confidence: 81%
See 2 more Smart Citations
“…Petrinovich & O'Neill (1996) found that participants were susceptible to the framing effect in the bystander scenario, and Pastötter et al (2013) showed that participants resisted the framing effect in the footbridge scenario. In line with these results, Cao et al (2017) confirmed that participants resisted framing manipulation in the 'footbridge scenario' while they were susceptible to the framing manipulation in the 'bystander scenario'. On the opposite, one study showed that participants resisted the framing manipulation in the 'bystander scenario' while they were susceptible to the framing manipulation in the 'footbridge scenario' (Broeders et al, 2011), which runs counter the aforementioned findings.…”
Section: Sinnott-armstrong 2011)supporting
confidence: 81%
“…If the framing effects have been widely studied in the field of moral decision making 1 , to our knowledge, only four studies have assessed their role in standard trolley-like dilemmas 2 , with the potential to afford cues about reliability of people's moral decisions (Broeders et al, 2011;Pastötter et al, 2013;Cao et al, 2017;Petrinovich & O'Neill, 1996). Results, however, are hardly conclusive.…”
Section: Sinnott-armstrong 2011)mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we introduced here a novel means of testing conviction in self-sacrifice – by measuring participants’ confidence in their decisions to self-sacrifice in a hypothetical trolley dilemma scenario in order to save the lives of ingroup members. We hope that this will contribute to the methodological discussions surrounding the use of trolley problem dilemmas (e.g., Gold et al, 2014b, 2015; Graham et al, 2016; Cao et al, 2017) and offer a valuable means of subtly testing precursor attitudes toward extremism.…”
Section: Discussionmentioning
confidence: 99%
“…Facing the exorbitant numbers of infected persons, a question was risen: How could medical care be provided equally if the number of infected is much higher than the number of ventilators available worldwide? Which lead the physicians to a re-discussion of the trolley dilemma [8,16] or the Doctor's Dilemma of George Bernard Shaw [17]: In the eventuality of two patients with respiratory failure and only one ventilator, which patient to save [18][19][20]?…”
Section: Introductionmentioning
confidence: 99%